Intervention in Syria: Russia Gambles Big Time - Dorsey, James Michael (2015)
The jury is still out on Russia’s gamble with its military intervention in Syria. Despite strained relations with the Middle East’s major Sunni Muslim powers, Turkey and Saudi Arabia, victory in Syria would demonstrate that Russia like the US is capable of projecting power beyond its borders. It’s a high risk gamble with the odds against it.